Kepercayaan dan Ritual Peziarah Makam Syekh Abdul Qodir di Desa Jambur di Padang Matinggi Kecamatan Panyabungan Utara Kabupaten Mandailing Natal - Lesnida, Lesnida; Parluhutan, Parluhutan; Salahuddin, Salahuddin (AHKAM, 2023)
The title of this research is Beliefs and pilgrimage rituals of the tomb of Sheikh Abdul Qodir in Jambur Padang Matinggi Village, North Panyabungan District, Mandailing Natal District. As for this research method, the researcher uses a research method, the method used is a qualitative method, using a type of field research (field research). This qualitative approach is expected to be able to produce information and describe the condition of the object of research at the time this research was carried out based on the facts as they were because of the purpose. The findings of this study are that pilgrims flock to the meal to pray so that what is expected can be fulfilled or get a dream ware or a sign to do something. However, some people do not really believe in and believe in things that are sacred or unseen, especially about praying and being eaten just to ask for a wish, some people think that this is heresy.